Modified mannan for 3D bioprinting: a potential novel bioink for tissue engineering. (19th August 2021) - Huang, Yuting; Zhou, Zheng; Hu, Yingbing; He, Ning; Li, Jing; Han, Xiaoxiao; Zhao, Guoqun; Liu, Hairong
Abstract: 3D bioprinting technology displays many advantages for tissue engineering applications, but its utilization is limited by veryfew bioinks available for biofabrication. In this study, a novel type of bioink, which includes three methacryloyl modifiedmannans, was introduced to 3D bioprinting for tissue engineering applications. Yeast mannan (YM) was modified by reactingwith methacrylate anhydride (MA) at different concentrations, and three YM derived bioinks were obtained, which weretermed as YM-MA-1, YM-MA-2 and YM-MA-3 and were distinguished with different adjusted methacrylation degrees. TheYM derived bioink displayed an advantage that the mechanical properties of its photo-cured hydrogels can be enhanced withits methacrylation degree. Hence, YM derived bioinks are fitted for the mechanical requirements of most soft tissueengineering, including cartilage tissue engineering. By selecting chondrocytes as the testing cells, well cytocompatibility of YM-MA-1, YM-MA-2 had been confirmed by CCK-8 method. Following photo-crosslinking and implantation into SD rats for 4 weeks, the in vivo biocompatibility of the YM-MA-2 hydrogel is acceptable for tissue engineering applications. Hence, YM-MA-2 was chosen for 3D bioprinting. Our data demonstrated that hydrogel products with designed shape and living chondrocytes have been printed by applying YM-MA-2 as the bioink carrying chondrocytes. After the YM-MA-2 hydrogel with encapsulated chondrocytes was implanted subcutaneously in nude mice for 2 weeks, GAG and COLII secretion was confirmed by histological staining in YM-MA-2-H, indicating that the YM derived bioink can be potentially applied to tissue engineering by employing a 3D printer of stereolithography.